Results of a 10 week community based strength and balance training programme to reduce fall risk factors: a randomised controlled trial in 65–75 year old women with osteoporosis. Issue 5 (1st October 2001) - Carter, N D; Khan, K M; Petit, M A; Heinonen, A; Waterman, C; Donaldson, M G; Janssen, P A; Mallinson, A; Riddell, L; Kruse, K; Prior, J C; Flicker, L; et al.
Abstract : Objective —To test the efficacy of a community based 10 week exercise intervention to reduce fall risk factors in women with osteoporosis. Methods —Static balance was measured by computerised dynamic posturography (Equitest), dynamic balance by timed figure of eight run, and knee extension strength by dynamometry. Subjects were randomised to exercise intervention (twice weekly Osteofit classes for 10 weeks) or control groups. Results —The outcome in 79 participants (39 exercise, 40 control) who were available for measurement 10 weeks after baseline measurement is reported. After confounding factors had been controlled for, the exercise group did not make significant gains compared with their control counterparts, although there were consistent trends toward greater improvement in all three primary outcome measures. Relative to the change in control subjects, the exercise group improved by 2.3% in static balance, 1.9% in dynamic balance, and 13.9% in knee extension strength. Conclusions —A 10 week community based physical activity intervention did not significantly reduce fall risk factors in women with osteoporosis. However, trends toward improvement in key independent risk factors for falling suggest that a study with greater power may show that these variables can be improved to a level that reaches statistical significance.